The investigation into the influence of the features of furniture product design on consumers' perceived value by fuzzy semantics - A. S. Lee (South African Journal of Business Management, 2014)
This study employed fuzzy theory to investigate the influence of the features of furniture product design on the fuzzy semantics of Taiwanese consumers' perceived value in new product design and development in hopes of providing product designers or developers with a reference to new product design and development. Furniture designers or manufacturers can use u(x), the fuzzy membership function value of the model for investigating the fuzzy semantic relation between the features of furniture product design and consumers' perceived value, to evaluate the fuzzy semantics of consumers' perceived value, and they can also employ the fuzzy semantic mean equation, namely to transform the research data into fuzzy semantics. In this study, all the consumers agreed that the features of furniture product design were significantly correlated to the fuzzy semantics of consumers' perceived value. In terms of the fuzzy semantics of the perceived value, the consumers with different genders, ages, education backgrounds, and incomes had different opinions about the features of furniture product design, and there were significant differences between the variables. In short, this study is helpful to understand consumers' demand for products as well as the development of consumer-oriented products, enhance their purchase intention, and improve corporate performance and market competitiveness.
Keywords: 650